Analysis of The Perspective of Uses and Gratification Theory and The Aida Model in Developing Spotify's Marketing Strategy - Amanda Ibel Anzela (Riviera Publishing, 2026)
The rapid development of digital music streaming platforms has fundamentally changed music consumption patterns, with Spotify emerging as the dominant player in Indonesia. This study aims to analyze Spotify's marketing strategy through the integrated lens of Uses and Gratifications Theory (UGT) and the AIDA (Attention, Interest, Desire, Action) model. A descriptive qualitative approach was employed, combining literature review and digital observation of Spotify's features, campaigns, and social media activities. The findings reveal that Spotify successfully meets users' needs for entertainment, personal identity, emotional escape, and ubiquity through personalized features such as Discover Weekly, mood-based playlists, and Spotify Wrapped. Simultaneously, Spotify implements an effective AIDA-based marketing strategy: capturing attention through viral campaigns like Wrapped and creative billboards, building interest via personalized content, creating desire by differentiating free and premium experiences, and encouraging action through free trials and affordable plans. However, the study also identifies weaknesses, including algorithmic filter bubbles that limit musical exploration and a lack of deep social interaction features compared to platforms like TikTok. The study concludes that the integration of UGT and AIDA provides a comprehensive framework for understanding Spotify's success in building user engagement and loyalty. Practically, the findings offer insights for digital platform managers to balance personalization with content diversity and community-building features.